Croatia Integrated State-Owned Enterprises Framework Assessment - World Bank (World Bank, Washington, DC, 2021)
The report provides one of the first comprehensive applications of the World Bank’s new integrated SOE framework (iSOEF) in Europe. Based on firm-level data, it provides analytical arguments indicating underperformance of the Croatian SOE sector, which ultimately stems from corporate governance deficiencies. As the report points to areas where reforms are of utmost importance and gives actionable policy recommendations, it is intended to be used for deepening the policy dialogue in the area of SOEs with Croatian authorities. The analysis covers non-financial companies with central government ownership of at least 50 percent. Short analysis of local government SOEs is given in Annex one. Long-term state asset management reform efforts intensified after 2013 with the intention to improve the SOEs management and reduce their fiscal burden. Also, two reforms were introduced in 2017, pertaining to the restructuring of the Central State Office for State Asset Management into the Ministry of State Assets, intended to foster a more coordinated approach and give impetus to the restructuring and privatization of SOEs; and the adoption of a new Corporate Governance Code. As of 2020, the Ministry of State Assets was merged with the Ministry of Construction and Physical Planning, and these reforms are yet to yield desired effects in terms of SOEs´ efficiency and return.